A Mosaic of Islamic Civilization in The Malaysia State - Armayanto, Harda; Al Faruqi, Achmad Reza Hutama; Ulfa, Maria; As Siddiq, Usamah; Munandar, M. Aldian (IAIN Syekh Nurjati Cirebon, 2023)
Malaysia is a country that has a geography that is not too big, but in the development of its civilization, Malaysia is one of the countries in Asia that has become the center of attention of Western scholars since the mid-19th Century. This article attempts to examine and review the development of Islamic civilization in Malaysia from a socio-historical perspective using descriptive and analytical methods. It was found that Malaysia has a unique society because they are a very polite type of society from countries in Asia, very kind, cleaner in the way they live and also beautiful, you could say Malaysia is a miniature of Asia. Therefore, this country is very interesting to study about the Islamic situation that is developing in it, it is found that there are already many Islamic universities that flow into various cultures and thoughts. It is certain that Malaysia has the roots of religious movements that accompany its civilization, with many of these roots being found in Islamic civilization. Seeing the development of Islam in Malaysia until it becomes the official religion reinforces this. Islam and Malay-Malaysia become a mosaic of identities that are inherent and cannot be separated from one another.